Improvement of dispersants on nano carbon black-modified cement paste: performance, microstructure and carbon footprint - Wang, Hui; Li, Chenjiang; Gao, Haixiang; Zhao, Yan; Xia, Handuo; Zhou, Cong; Zhong, Shunjie; Zhao, Qingxin (Frontiers in Materials, 2024)
The agglomeration of nano carbon black (NCB), driven by its high specific surface energy, limits the fundamental performance of cementitious materials and hinders the broader application of functional cementitious materials in engineering domains. NCB-modified cement (NC) has a low snow-melting efficiency, resulting in high energy consumption and excessive CO2 emissions. Herein, this study innovatively proposed a method of using dispersants to overcome the above issue and systematically introduced the effects of three dispersants, polycarboxylic acid superplasticizer (PCE), tannic acid (TA), and sodium dodecyl sulfate (SDS), on NC. The dispersity of dispersant-NCB suspension was analyzed firstly, and then the performance of fresh paste, mechanical properties, resistivity, snow-melting speed and LCA of NC were explored. Experimental results indicated that, in terms of suspension stability, SDS was the most effective, followed by TA, while PCE exhibited the least efficacy. Furthermore, all three dispersants improved the fluidity of NC to varying degrees. However, PCE and TA demonstrated a retardation effect on the setting time, whereas SDS facilitated a reduction in the setting time of NC. From the point of view of mechanical properties, the use of these dispersants not only augmented the mechanical strength of the NC but also decreased its electrical resistivity. The uniform dispersion of SDS at the microstructural level of NCB had also been found. When the PCE content is 0.2%, TA content is 0.4%, and SDS content is 0.4%, the mechanical strength and resistivity of NC were the best. NC with dispersant TA melted snow three times faster than the control group, reducing snow-melting energy consumption. Moreover, LCA analysis showed that the addition of dispersants also reduced carbon emissions.